EFFECTIVE WAYS TO LEARN AND RETAIN GROSS ANATOMY - Alia Amin (Army Medical College Rawalpindi, 2019)
Anatomy is a basic science subject taught in preclinical years in undergraduate medical education. It is considered a vast, dry and volatile subject that is full of anatomical jargon/nomenclature and factual information to be remembered. By the time students start their clinical attachments, most of anatomy is forgotten. Good knowledge of anatomy is essential to understand other basic and clinical science subjects. It holds pivotal importance to provide effective learning opportunities to the students through active, collaborative and reflective (A-C-R) approach towards teaching for lifelong learning. This guide provides some tips based on principles of learning and cognitive psychology, to learn and retain gross anatomy. It can be useful both for the teachers and students.